IMF Membership in the Financial Stability Board. (Policy Papers; Policy Paper ;, 2013)
In light of the recent establishment of the Financial Stability Board (FSB) as an association under Swiss law, this paper proposes Fund membership in the new association. The FSB was formed in 2009 and the Fund's Executive Board approved the Fund's membership in 2010, which has provided the Fund with the necessary scope to engage and collaborate with the FSB on a wide range of issues of mutual interest. Recently, in response to a request by the G-20 to establish the FSB with a well-defined 'legal personality,' the FSB was established as an association under Swiss law. In light of this change, an Executive Board decision is required for the Fund to formally join the Association.